1979
DOI: 10.1007/bf01326894
|View full text |Cite
|
Sign up to set email alerts
|

Radioprotection by DMSO of mammalian cells exposed to X-rays and to heavy charged-particle beams

Abstract: Populations of G1-phase Chinese hamster cells in stirred suspensions containing various concentrations of DMSO were irradiated with 250 kV X-rays or various heavy charged-particle beams. Chemical radioprotection of cell inactivation was observed for all LET values studied. When cell survival data were resolved into linear and quadratic components, the extent and concentration dependence of DMSO protection were found to be different for the two mechanisms. The chemical kinetics of radioprotection for single-eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(28 citation statements)
references
References 18 publications
1
26
0
Order By: Relevance
“…Using particle beams of H 2 +, Li3+, c 6 +, Ne 10 +, and Ar 18 + of initial energies from 8.5 to 570 MeV/u, Roots et al (198Gb, 1981) found that the contribution to cell killing by hydroxyl radicals was highly dependent on particle velocity and atomic number, but that the results did not correlate well with LEToo for the high energy particles. Although, in general, the fraction of the total radiation damage caused by hydroxyl radicals decreased with increasing LET as has also been shown by others (Brustad, 1962;Manney et al, 1963;Takeshita and Sawada, 1974;Singh et al, 1976;Chapman et al, 1979). In ~he case of the low energy particle beams where fragmentation is minimal, the decrease in the extent of hydroxyl-radical induced cell lethality with respect to LET, corresponded to the decrease in G(OH) values from Vereschinskii and Pikaev (1964) as a function of LET.…”
Section: F Radiosensitizers and Radioprotectorssupporting
confidence: 53%
See 3 more Smart Citations
“…Using particle beams of H 2 +, Li3+, c 6 +, Ne 10 +, and Ar 18 + of initial energies from 8.5 to 570 MeV/u, Roots et al (198Gb, 1981) found that the contribution to cell killing by hydroxyl radicals was highly dependent on particle velocity and atomic number, but that the results did not correlate well with LEToo for the high energy particles. Although, in general, the fraction of the total radiation damage caused by hydroxyl radicals decreased with increasing LET as has also been shown by others (Brustad, 1962;Manney et al, 1963;Takeshita and Sawada, 1974;Singh et al, 1976;Chapman et al, 1979). In ~he case of the low energy particle beams where fragmentation is minimal, the decrease in the extent of hydroxyl-radical induced cell lethality with respect to LET, corresponded to the decrease in G(OH) values from Vereschinskii and Pikaev (1964) as a function of LET.…”
Section: F Radiosensitizers and Radioprotectorssupporting
confidence: 53%
“…10. Combined application of drugs~ hyperthermia, anisotonic solutions, time delay, and radiations including sequential treatments of heavy ions and X rays (Chapman et al, 1977(Chapman et al, , 1978(Chapman et al, , 1979Gerner and Leith, 1977;Guichard et al, 1982;Ngo et al, 1981;Roots et al, 1982;Schroy et al, 1980b;Tenforde et al, 1981bTenforde et al, , 1982b). …”
Section: Heavy Ion Radiobiology Of Cells At the Bevalacmentioning
confidence: 99%
See 2 more Smart Citations
“…The indirect eVect of hydroxyl radicals is known to play unlike the more localized expression of phosphorylated H3. These data represent our rst attempts a major role (~85%) in cell killing by the single-hit mechanism (Chapman et al 1979, Chapman 1980. to quantify molecular factors that are uniquely expressed when chromatin is compacted for And when chromatin is compacted, the probability of producing multiply damaged, irreparable lesions correlation with increased radiation sensitivity.…”
Section: Discussionmentioning
confidence: 98%